2015
DOI: 10.1017/s1041610214002555
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging biomarkers for dementia with Lewy bodies: an update

Abstract: Most of the above nuclear imaging methods are restricted to highly specialized clinical centers, and thus not applicable to a large number of patients requiring dementia (e.g. DLB) diagnosis in routine clinical setting. Validating them against more readily accessible peripheral biomarkers, e.g. CSF and blood biomarkers linked to the DLB process, may facilitate their use in wider clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 143 publications
(150 reference statements)
0
2
0
Order By: Relevance
“…DLB is a common cause of dementia, accounting for 4%–8% of dementia cases (McKeith et al , 2007 ), and it is characterized by three core clinical symptoms: cognitive fluctuations, visual hallucinations, and Parkinsonism (McKeith et al , 2005 ). There is now a growing body of neuroimaging research on DLB where this dementia is compared with AD in order to improve differential diagnosis between these two conditions, as well as to further our understanding of their neurobiological divergences (Mukaetova-Ladinska, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…DLB is a common cause of dementia, accounting for 4%–8% of dementia cases (McKeith et al , 2007 ), and it is characterized by three core clinical symptoms: cognitive fluctuations, visual hallucinations, and Parkinsonism (McKeith et al , 2005 ). There is now a growing body of neuroimaging research on DLB where this dementia is compared with AD in order to improve differential diagnosis between these two conditions, as well as to further our understanding of their neurobiological divergences (Mukaetova-Ladinska, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lewy body dementia (LBD) affects about 1.3 million Americans and their families, making it the most common form of non-Alzheimer’s dementia [1]. Few studies have been conducted on the role of the apolipoprotein E ( APOE ) ε4 allele in LBD, but following the trajectory of past studies in Alzheimer’s disease (AD), researchers have shown that the inheritance of the ε4 allele increases a person’s risk of developing LBD [24] and is associated with an earlier age of death for people diagnosed with LBD [4].…”
Section: Introductionmentioning
confidence: 99%